Punicalagin Induces Nrf2/HO-1 Expression via Upregulation of PI3K/AKT Pathway and Inhibits LPS-Induced Oxidative Stress in RAW264.7 Macrophages - Xiaolong Xu; Hongquan Li; Xiaolin Hou; Deyin Li; Shasha He; Changrong Wan; Peng Yin; Mingjiang Liu; Fenghua Liu; Jianqin Xu (Hindawi Limited, 2015)
Reactive oxygen species (ROS) and oxidative stress are thought to play a central role in potentiating macrophage activation, causing excessive inflammation, tissue damage, and sepsis. Recently, we have shown that punicalagin (PUN) exhibits anti-inflammatory activity in LPS-stimulated macrophages. However, the potential antioxidant effects of PUN in macrophages remain unclear. Revealing these effects will help understand the mechanism underlying its ability to inhibit excessive macrophage activation. Hemeoxygenase-1 (HO-1) exhibits antioxidant activity in macrophages. Therefore, we hypothesized that HO-1 is a potential target of PUN and tried to reveal its antioxidant mechanism. Here, PUN treatment increased HO-1 expression together with its upstream mediator nuclear factor-erythroid 2 p45-related factor 2 (Nrf2). However, specific inhibition of Nrf2 by brusatol (a specific Nrf2 inhibitor) dramatically blocked PUN-induced HO-1 expression. Previous research has demonstrated that the PI3K/Akt pathway plays a critical role in modulating Nrf2/HO-1 protein expression as an upstream signaling molecule. Here, LY294002, a specific PI3K/Akt inhibitor, suppressed PUN-induced HO-1 expression and led to ROS accumulation in macrophages. Furthermore, PUN inhibited LPS-induced oxidative stress in macrophages by reducing ROS and NO generation and increasing superoxide dismutase (SOD) 1 mRNA expression. These findings provide new perspectives for novel therapeutic approaches using antioxidant medicines and compounds against oxidative stress and excessive inflammatory diseases including tissue damage, sepsis, and endotoxemic shock.